Psychodynamic Approach, Social Cognitive and Neurobiology Aspect of Tantrum Behaviour in Children - Budi Pratiti (Scientia Psychiatrica, 2020)
One form of emotional expression in the form of explosive anger in children is known as tantrum behaviour, which can be categorized as bad behaviour based on the perspective of some parents. This is very much related to the problem of child despair, which is caused by the way parents are not quite right in responding to tantrums, so the child reacts inappropriately. Parental responses make children increasingly undisciplined, even this provides opportunities for children to find certain ways to get their desires in a negative way. The child's inability to communicate is one aspect of tantrum studies. This communication is more translated as an expression of emotion and better known as tantrum. This article review will discuss temper tantrum behaviour in children along with a review of various theoretical points of view.